2014
DOI: 10.4049/jimmunol.1302561
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immunity and CD4+ Th1 Cells Are Both Necessary for a Fully Protective Immune Response upon Secondary Infection with Brucella melitensis

Abstract: Brucella spp are intracellular bacteria that cause brucellosis, one of the most common zoonoses in the world. Given the serious medical consequences of this disease, a safe and effective human vaccine is urgently needed. Efforts to develop this vaccine have been hampered by our lack of understanding of what constitutes a protective memory response against Brucella. In this study, we characterize the cells and signaling pathways implicated in the generation of a protective immune memory response following primi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 93 publications
2
86
0
1
Order By: Relevance
“…At 28 d p.i., both groups were treated daily with a combination of antibiotics (see Materials and Methods) for 2 wk to eliminate the Brucella. As shown previously (17), this treatment led to the complete elimination of Brucella in all tested organs of the infected mice. After a rest period of 2 wk, control mice and previously infected mice were challenged with an mCherry-Br strain of B. melitensis.…”
Section: Intranasal Brucella Infection Induces Protective Memory Actimentioning
confidence: 63%
See 4 more Smart Citations
“…At 28 d p.i., both groups were treated daily with a combination of antibiotics (see Materials and Methods) for 2 wk to eliminate the Brucella. As shown previously (17), this treatment led to the complete elimination of Brucella in all tested organs of the infected mice. After a rest period of 2 wk, control mice and previously infected mice were challenged with an mCherry-Br strain of B. melitensis.…”
Section: Intranasal Brucella Infection Induces Protective Memory Actimentioning
confidence: 63%
“…Previous studies by our group using an i.p. B. melitensis infectious model with the same B. melitensis strain (17) showed that genetic deficiencies leading to a lack of CD4 + T cells (MHCII infected with wt B. melitensis 28 d previously and treated with antibiotics as described previously were challenged with mCherry-B. melitensis.…”
Section: Brucella Infectionmentioning
confidence: 99%
See 3 more Smart Citations